The integration of content and English in the teaching of information technology subjects at polytechnics and community colleges in Malaysia - Wan Omar, Wan Nor Aishah (2016)
This mixed-methods study investigates the teaching of Iinformation Technology (IT) subjects at polytechnics and community colleges in Malaysia as the policy for the medium of instruction for Science, Mathematics and Technical subjects at primary and seconday education sector changed from Bahasa Malaysia to English in 2003 and back to Bahasa Malaysia again in 2009. However, as polytechnics and community colleges are under the Ministry of Higher Education (MoHE), they are guided by the Malaysia Education Blueprint 2015-2025 (Higher Education) (2015). The higher learning institutions in Malaysia do not clearly define English or Bahasa Malaysia as the only medium of instruction due to factors such as internationalization and the needs to be able to produce globally competitive graduates. Due to these factors, the use of English or bilingualism at higher education sector becomes necessary. This research provides an insight into the transition period when the polytechnics and community colleges started receiving the first batch of students who had gone through ETeMS in 2008, and therefore, the lecturers were required to teach Technical subjects through English. The objectives of the study are to investigate the attitudes and motivation levels of the lecturers at polytechnics and community colleges in Malaysia with regards to the policy of teaching IT subjects through English, to examine the strategies the lecturers used to upgrade their English and to explore the strategies the lecturers used to teach their subjects through English.